2024
DOI: 10.3389/fphar.2024.1331622
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a vaginal suppository formulation prepared with Acacia arabica (Lam.) Willd. gum and Cinnamomum camphora (L.) J. Presl. in heavy menstrual bleeding analyzed using a machine learning technique

Mohamed Joonus Aynul Fazmiya,
Arshiya Sultana,
Md Belal Bin Heyat
et al.

Abstract: Objective: This study aims to determine the efficacy of the Acacia arabica (Lam.) Willd. and Cinnamomum camphora (L.) J. Presl. vaginal suppository in addressing heavy menstrual bleeding (HMB) and their impact on participants' health-related quality of life (HRQoL) analyzed using machine learning algorithms.Method: A total of 62 participants were enrolled in a double-dummy, single-center study. They were randomly assigned to either the suppository group (SG), receiving a formulation prepared with Acacia arabic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…The main cause of various chronic disorders is an increase in the free radical concentration inside cells including reproductive-related problems. Antioxidant phytochemicals reduce the progress of many chronic diseases by neutralizing free radicals ( Sultana et al, 2022b ; Fazmiya et al, 2024 ) ( Figure 8 ). Zahra et al suggested that the effects of ROS involve biological roles as weapons in the arsenal of the immune system ( Zahra et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main cause of various chronic disorders is an increase in the free radical concentration inside cells including reproductive-related problems. Antioxidant phytochemicals reduce the progress of many chronic diseases by neutralizing free radicals ( Sultana et al, 2022b ; Fazmiya et al, 2024 ) ( Figure 8 ). Zahra et al suggested that the effects of ROS involve biological roles as weapons in the arsenal of the immune system ( Zahra et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In biology, the analytical and predictive capabilities of AI models have been empirically demonstrated across multiple research directions ( Ukwuoma et al, 2022b ; 2022a ; 2023 ; Fazmiya et al, 2024 ; Heyat et al, 2024 ; Sumbul et al, 2024 ). Based on this, we propose an innovative hybrid neural network model, STM-ac4C, designed to accurately identify N4-acetylcytidine (ac4C) modification sites on human mRNA.…”
Section: Methodsmentioning
confidence: 99%